2022
DOI: 10.3390/ijms232012286
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Placental Lipid Hydrolysis by High-Fat/High-Cholesterol Feeding and Gestational Diabetes Mellitus in Mice

Abstract: Advanced maternal age and obesity are the main risk factors to develop gestational diabetes mellitus (GDM). Obesity is a consequence of the increased storage of triacylglycerol (TG). Cytosolic and lysosomal lipid hydrolases break down TG and cholesteryl esters (CE) to release fatty acids (FA), free cholesterol, and glycerol. We have recently shown that intracellular lipases are present and active in the mouse placenta and that deficiency of lysosomal acid lipase alters placental and fetal lipid homeostasis. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…There are some conflicting findings in the literature about fetal weight in GDM mice. Some studies reported that higher fetal weight or macrosomia were observed in GDM mice, studies using high-fat diets to construct obese GDM mice have found that altered glucose, amino acid, and fatty acid transport in the placenta stimulates the release of endogenous insulin-like growth factor-1 by the fetus, resulting in fetal overgrowth, which is an explanation to some extent for the development of macrosomia in overweight GDM patients ( 11 , 43 , 44 ). In contrast, other studies showed fetal weight was decreased in GDM mice ( 45 ), and a large clinical study of 11,486 pregnant women found that newborns with GDM had a 1.6 times higher risk of low birth weight than normal pregnant women ( 8 ), but the mechanism by which this occurs has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…There are some conflicting findings in the literature about fetal weight in GDM mice. Some studies reported that higher fetal weight or macrosomia were observed in GDM mice, studies using high-fat diets to construct obese GDM mice have found that altered glucose, amino acid, and fatty acid transport in the placenta stimulates the release of endogenous insulin-like growth factor-1 by the fetus, resulting in fetal overgrowth, which is an explanation to some extent for the development of macrosomia in overweight GDM patients ( 11 , 43 , 44 ). In contrast, other studies showed fetal weight was decreased in GDM mice ( 45 ), and a large clinical study of 11,486 pregnant women found that newborns with GDM had a 1.6 times higher risk of low birth weight than normal pregnant women ( 8 ), but the mechanism by which this occurs has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Placental FA transport relies mainly on the activity of lipid hydrolases in the syncytiotrophoblast MVM and FA uptake by various FA transport proteins [FA transporters (FATs), FA binding proteins (FABPs), and FA transport proteins (FATPs), etc. ] in the plasma membrane[ 34 - 36 ].…”
Section: Impacts Of Gdm On Placental Transport Functionmentioning
confidence: 99%
“…Experiments on human placental explants have shown that the activity of carnitine palmitoyltransferase is inhibited by hyperglycemia, such that β-oxidation is reduced and esterification pathways are increased, leading to the accumulation of placental TG[ 39 ]. Another animal experiment showed that maternal mice fed a high-fat/high-cholesterol diet (accompanied or not accompanied by GDM) had dysregulated placental lipid hydrolase activity, increased cholesteryl ester hydrolase activity, and decreased TG hydrolase activity; as such, excessive cholesterol was input into the offspring, resulting in an increase in liver lipids and the accumulation of placental TG, which may cause overgrowth[ 36 ]. These findings indicate that the oxidation of FAs is reduced and that the expression of placental proteins and TG hydrolases becomes imbalanced, which causes the deposition of placental TG; moreover, although maternal TG does not pass through the placenta, it can be decomposed by placental LPL, TG hydrolases and other lipases and subsequently infiltrate the placenta.…”
Section: Impacts Of Gdm On Placental Transport Functionmentioning
confidence: 99%
“…[30] Clinical studies and animal experiments have shown that, total fat, including triglycerides and cholesterol, is an independent risk factor for adverse pregnancy outcomes in patients with GDM. [29,[31][32][33][34] Some studies suggest that a diet high in total fat and saturated fatty acids may increase the risk of developing GDM. [35][36][37][38][39] Polyunsaturated fatty acids and monounsaturated fatty acids in place of saturated fatty acids are associated with a reduced risk of developing GDM.…”
Section: Polyunsaturated Fatty Acidmentioning
confidence: 99%